DOES CUSTOMERS SATISFACTION MEDIATE THE RELATIONSHIP BETWEEN HEDONIC AND UTILITARIAN VALUES TO BEHAVIORAL INTENTION? - Dewi, Fatikha Rizdiana; Fatmawati, Indah (Jurnal Manajemen Bisnis, 2019)
This study investigated the effects of hedonic and utilitarian values on behavioral intentions and the mediating effects of satisfaction in the restaurant industry. A survey was conducted in the setting of culinary industry. Purposive sampling method was used to collect 125 samples. The data was analyzed using linier regression.            The result showed that the hedonic and utilitarian value has a significant and positive direct effect on satisfaction. The hedonic and utilitarian values, and the satisfaction as well also have significant and positive effect on behavioral intention. This study also showed that customer satisfaction acts as a partial mediator in the relationship between hedonic value and utilitarian value on behavioral intentions.